Basal leg blood flow in healthy women is related to age and hormone replacement therapy status - Moreau, Kerrie L (Blackwell Science Inc, 2003)
Basal leg blood flow declines with age in healthy men, an effect that is mediated by augmented sympathetic vasoconstriction. However, in women the presence or absence of oestrogen and selective use of hormone replacement therapy (HRT) may alter these relationships with ageing. We studied 103 healthy women: 73 postmenopausal (41 HRT, mean ± s.e.m. 61 ± 1 years; 32 no-HRT, 63 ± 2 years) and 30 premenopausal (29 ± 1 years). Compared with the premenopausal controls, absolute femoral artery blood flow (duplex ultrasound) was 23 % lower (P < 0.001) in the postmenopausal no-HRT group, but only 13 % lower in the HRT group (P < 0.01). The age and HRT group differences in leg blood flow were consistently associated with differences in leg vascular conductance, but not with femoral artery lumen diameter, leg muscle sympathetic nerve activity or cardiac output (systemic arterial blood flow). Leg fat-free mass was smaller in the postmenopausal groups (P < 0.05). Femoral blood flow normalized for leg fat-free mass was 17 % lower (P < 0.01) in the postmenopausal no-HRT compared with the premenopausal women, but was not different in the postmenopausal HRT and premenopausal groups. Femoral artery shear stress was similar in the postmenopausal HRT and premenopausal women, but was lower in the postmenopausal no-HRT group (P < 0.01). Basal whole-leg blood flow declines with age in healthy, oestrogen-deficient women, a phenomenon that is mediated primarily by reductions in leg vascular conductance. Among postmenopausal women, chronic HRT use is associated with augmented basal leg blood flow and vascular conductance. Leg blood flow normalized for leg fat-free mass is preserved with age in women taking chronic HRT. In contrast to men, differences in leg sympathetic vasoconstrictor nerve activity do not explain group differences in leg blood flow and vascular conductance with ageing in women.